Women’s Labour, British Naval Hospital Ships, and a System of Medical Care, 1775-1815 - Spinney, Erin Elizabeth (The Northern Mariner / Le marin du nord, 2023)
This research note uses new methodologies to investigate the presence of women nurses and other labourers on British hospital ships during the Revolutionary and Napoleonic Wars. Using pay lists, musters, and log book records, it is possible to track the work of women labourers throughout the naval medical system of care. The work of women on these ships challenges our previous assumptions concerning medical care in the late eighteenth and early nineteenth centuries. Cette note de recherche fait appel à de nouvelles methodologies pour enquêter sur la présence des infirmières et des autres ouvrières sur les navires hospitaliers britanniques pendant les guerres révolutionnaires et napoléoniennes. À l’aide de listes de paye, de listes des membres d’équipage et de registres des journaux de bord, il est possible de suivre le travail des femmes dans tout le système de soins médicaux de la marine. Le travail des femmes sur ces navires nous oblige à revoir nos suppositions antérieures concernant les soins médicaux à la fin du 18e et au début du 19e siècle.